2020
DOI: 10.1038/s41467-019-14027-y
|View full text |Cite
|
Sign up to set email alerts
|

Natural variation of an EF-hand Ca2+-binding-protein coding gene confers saline-alkaline tolerance in maize

Abstract: Sodium (Na + ) toxicity is one of the major damages imposed on crops by saline-alkaline stress. Here we show that natural maize inbred lines display substantial variations in shoot Na + contents and saline-alkaline (NaHCO 3 ) tolerance, and reveal that ZmNSA1 (Na + Content under Saline-Alkaline Condition) confers shoot Na + variations under NaHCO 3 condition by a genome-wide association study. Lacking of ZmNSA1 promotes shoot Na + homeostasis by increasing root Na + efflux. A naturally occurred 4-bp deletion d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
86
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(87 citation statements)
references
References 59 publications
1
86
0
Order By: Relevance
“…Natural maize varieties confer a rich genetic diversity of salt tolerance, which is due mostly to the functional variation of genes mediating SIOS tolerance and Na + homeostasis (Saneoka et al ., 1995; Luo et al ., 2019; C. Zhang et al ., 2019; M. Zhang et al ., 2019; Sandhu et al ., 2020). Our previous studies showed that maize ZmNC1 ( Na + Content 1 ), ZmNC2 and ZmNSA1 ( Na + Content under Saline‐Alkaline Condition ) underlie the natural variation of the shoot Na + exclusion, a key process protecting shoot tissue from Na + toxicity (Zhang et al ., 2018; C. Zhang et al ., 2019; M. Zhang et al ., 2019; Cao et al ., 2020). In this study, we aimed to use metabolites as biomarkers to investigate the genetic basis underlying the natural variation of SIOS tolerance in maize (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Natural maize varieties confer a rich genetic diversity of salt tolerance, which is due mostly to the functional variation of genes mediating SIOS tolerance and Na + homeostasis (Saneoka et al ., 1995; Luo et al ., 2019; C. Zhang et al ., 2019; M. Zhang et al ., 2019; Sandhu et al ., 2020). Our previous studies showed that maize ZmNC1 ( Na + Content 1 ), ZmNC2 and ZmNSA1 ( Na + Content under Saline‐Alkaline Condition ) underlie the natural variation of the shoot Na + exclusion, a key process protecting shoot tissue from Na + toxicity (Zhang et al ., 2018; C. Zhang et al ., 2019; M. Zhang et al ., 2019; Cao et al ., 2020). In this study, we aimed to use metabolites as biomarkers to investigate the genetic basis underlying the natural variation of SIOS tolerance in maize (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, future validation of the rest of the sulfotransferase ZmSOT candidates will facilitate the structural identification of these METOs as well as advance our understanding of the metabolomics and genetic basis underlying the natural variation of maize SIOS tolerance. In the long run, marker‐assisted breeding programs could introgress the SIOS‐tolerant alleles of ZmSOTs and previously identified genetic variants promoting Na + homeostasis into high‐yielding maize cultivars to develop commercial hybrids (Zhang et al ., 2018; C. Zhang et al ., 2019; M. Zhang et al ., 2019; Cao et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…S6, A and B). HKTs regulate long-distance Na 1 delivery, depending on root-toshoot Na 1 translocation and Na 1 exclusion from the reproductive organ (Cao et al, 2020). HvHKT1;5 negatively regulates salt tolerance in barley (Huang et al, 2020).…”
Section: Hvcam1 Regulates Na 1 Transport Via Preferential Transcriptimentioning
confidence: 99%
“…Allelic variations in untranslated region (UTR) also play a pivotal role in gene expression regulation. In maize, a naturally occurred 4‐bp deletion in the 3′UTR of ZmNSA1 ( Na + Content under Saline‐Alkaline Condition ) reduces the translation efficiency of ZmNSA1 and consequently promotes Na + homeostasis under saline‐alkaline condition (Cao et al ., 2020). UTRs are generally involved in post‐transcriptional regulation such as messenger RNA (mRNA) stability, mRNA transport, and translation efficiency (Srivastava et al ., 2018) and therefore have a larger role than transcript level control.…”
Section: Introductionmentioning
confidence: 99%